Assessment of Salivary Neutrophil Gelatinase-Associated Lipocalin Levels in Diseased and Healthy Periodontium - Al-Musawi, Muntadhr; Ali, Omar (AL-Kindy College Medical Journal, 2024)
Background: periodontal disease is one of the most frequent human diseases. Depending on the severity of the inflammation, the destructive process may affect both the gingiva (gingivitis) and/or the periodontal ligament and alveolar bone that surround and support the teeth (periodontitis).Objective: The study aimed to determine and compare the level of salivary Neutrophil gelatinase-associated lipocalin in periodontal health and disease (gingivitis and periodontitis stage I-III).Subjects and Methods: A total of 90 individuals participated in the research separated into five groups, clinically healthy (n=10), gingivitis (n=20), stage I periodontitis (n=20), stage II periodontitis (n=20) and stage III periodontitis (n=20), periodontal parameters were recorded, and the level of salivary Neutrophil gelatinase-associated lipocalin was assessed by using the enzyme-linked immunosorbent assay.Results: Neutrophil gelatinase-associated lipocalin salivary level was significantly higher (p